2021
DOI: 10.1016/j.jbc.2021.100942
|View full text |Cite
|
Sign up to set email alerts
|

The innate immune kinase TBK1 directly increases mTORC2 activity and downstream signaling to Akt

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 78 publications
0
13
0
Order By: Relevance
“…In contrast, Tooley et al. ( 6 ) found that EGF stimulation did not enhance S172 phosphorylation, supporting that it is the basal activity of TBK1 that is important for mTORC2 signaling downstream of growth factors. However, when RAW264.7 macrophages and primary bone marrow–derived macrophages were stimulated with the dsRNA mimetic poly(I:C), which induces TBK1-S172 phosphorylation, TBK1 and mTOR-S2159 were also found to be required for mTORC2-dependent phosphorylation of Akt-S473.…”
mentioning
confidence: 96%
See 4 more Smart Citations
“…In contrast, Tooley et al. ( 6 ) found that EGF stimulation did not enhance S172 phosphorylation, supporting that it is the basal activity of TBK1 that is important for mTORC2 signaling downstream of growth factors. However, when RAW264.7 macrophages and primary bone marrow–derived macrophages were stimulated with the dsRNA mimetic poly(I:C), which induces TBK1-S172 phosphorylation, TBK1 and mTOR-S2159 were also found to be required for mTORC2-dependent phosphorylation of Akt-S473.…”
mentioning
confidence: 96%
“…Therefore, the authors conclude that under both basal and activated states, the activation of Akt by TBK1 is mediated through mTORC2 ( Fig. 1 ) ( 6 ).
Figure 1 TBK1 promotes AKT activation through mTORC2.
…”
mentioning
confidence: 97%
See 3 more Smart Citations